Willingness to pay for solar off-grid lighting in rural India - Abraham, Pleasa Serin; Gundimeda, Haripriya; Venkateshwaran, Jayendran; Solanki, Chetan Singh (Asian Development Policy Review, 2024)
This paper attempts to quantitatively determine the factors that affect the adoption of solar off-grid lighting products from the experience of using solar study lamps. The discrete choice experiment method is applied where the rural household in the primary survey is asked to reveal their willingness to pay for solar off-grid lighting products like Solar Pocket lamp, Solar Hurricane lamp, and Solar Home Lighting System (SHLS) in the pre-intervention and post-intervention stages. The baseline (pre-intervention) and impact (post-intervention) data helps to check whether exposure to the use of solar off-grid product technology will improve familiarity and boosts confidence, which in turn results in a higher willingness to pay for the products. The data analysis using Tobit regression reveals that the willingness to pay significantly rises in the post-intervention phase in the case of all three products. This study examines the factors influencing ‘base of pyramid’ households' willingness to pay for solar off-grid lighting systems in India. Using data collected from 663 households, it is identified that the money spent on kerosene lighting, electricity reliability, household type, total assets, and knowledge of the health effects of kerosene, the specification of the solar panel, the number of solar lamps, and the functioning status of the study lamp are major determinants of the willingness to pay for solar off-grid technologies.